CORRELATIONAL BETWEEN QUIZIZZ AS DIGITAL PLATFORM FOR LEARNING ENGLISH TOWARDS READING ABILITY: A Study at Eight Grade of SMP Negeri 11 Surakarta the Academic Year 2022/2023 - Zahra Putri Ayuningtyas; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
The aimed of this research was to determine (1) Quizizz application in learning English of the eight grade SMP N 11 Surakarta, (2) to find out the students’ reading ability of the eight grade of SMP N 11 Surakarta, and (3) to find out whether or not there is correlation of study between Quizizz and students’ reading ability of students in graden 8 SMP Negeri 11 Surakarta in the Academic year 2022/2023. This researcher was conducted at the eight grade of SMP Negeri 11 Surakarta in the academic year 2022/2023. Researcher used quantitative methods with correlation techniques. The researcher give questionnaire to 30 participants in order to gather the data quizizz in learning reading English in a class. The questionnaire used consisted of 30 items. Then, to measure the ability reading students, this research used a reading test for students. In data analysis, students’ questionnaires were measured using a Likert Scale, and reading tests were measured using Suharsimi Arikunto’s categories reading achievement. The findings of this research indicate that there are positive about correlation of research between quizizz and students’ reading English ability. It is proven by the results of calculation of ((rxy) 0.615) > rtable in the significant table 5% (0.374) and 1% (0.478). Then, it can be concluded that the alternative hypothesis (Ha) is therefore deemed to be accepted and the null hypothesis (Ho) is rejected. Therefore, in this research it can be concluded that there is a positive the correlation of research between quizizz as digital platform and students’ reading English ability. This means quizizz has higher impact, the better students’ reading ability. Keywords : Quizizz, Reading English Ability, Correlational Study